2014
DOI: 10.1371/journal.pone.0099580
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in PVRL2-TOMM40-APOE Region Are Associated with Human Longevity in a Han Chinese Population

Abstract: PurposeHuman longevity results from a number of factors, including genetic background, favorable environmental, social factors and chance. In this study, we aimed to elucidate the association of human longevity with genetic variations in several major candidate genes in a Han Chinese population.MethodsA case-control association study of 1015 long-lived individuals (aged 90 years or older) and 1725 younger controls (30–70 years old) was undertaken. Rs2075650 in TOMM40 was firstly genotyped using the ABI SNaPsho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Several genome-wide association studies have associated tag SNPs in the cluster of genes PVRL2, TOMM40, APOE, and APOC1 in chromosome 19 to EL (40,(46)(47)(48), and some investigators have hypothesized that these variants may be important for EL independently of the APOE alleles ε ε ε…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genome-wide association studies have associated tag SNPs in the cluster of genes PVRL2, TOMM40, APOE, and APOC1 in chromosome 19 to EL (40,(46)(47)(48), and some investigators have hypothesized that these variants may be important for EL independently of the APOE alleles ε ε ε…”
Section: Discussionmentioning
confidence: 99%
“…, , . For example, Lu et al used haplotype analysis of SNPs tagging this region to conjecture that PVRL2, TOMM40, in addition to APOE, may be important for EL (48). In a recent meta-analysis of four genome-wide association studies of EL (37), we identified a large cluster of SNPs in this region that was significantly associated with EL and, by examining their patterns of linkage disequilibrium, we identified two most significantly associated SNPs with EL (Supplementary Figure 6A).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Poolseq with target region including regulatory region such as proximal upstream and intronic region identified longevity-associated common variants, rs405509 and rs769449 that were previously associated with longevity and other aging-related disease phenotypes (Lu et al, 2014; Soerensen et al, 2013). They are also predicted (Supplementary Figure 2) and experimentally proved (Supplementary Table 3) to be functional, implicating the potential role of regulatory variants in a longevity-association.…”
Section: Descriptionmentioning
confidence: 99%
“…Davies et al (2015) using the large subject number and meta-analysis, also demonstrated a significant and increased correlation between general cognitive function with increased cohort age, compared to the youngest age groups, with the cognitive effect size being related to rs10119, the most major SNP located in the ApoE/TOMM40 region. Roses et al (2010) and Lu et al (2014) have further shown that TOMM40 gene has long and short variants, combinations of which appear to contribute to earlier presentation and shorter life expectancy with late onset of Alzheimers disease (LOAD), and although the mechanisms involved have not to date been elucidated, the earlier presenting variants are considered to be more closely associated with its lipidassociated effects (Yu et al 2013;Bekris et al 2012).…”
Section: Apoe Epigenetics and Longevitymentioning
confidence: 99%